Four-Horse Evener for Wheel-Plows - Wolcott, Oliver P. (United States. Patent Office., 1905)
Patent for a four horse evener for wheel plows that improves disk or moldboard. It corrects the plows tendency to swing when met with the ground and utilizes the same force to relieve strain from the horses.